History of modern design : graphics and products since the Industrial Revolution / David Seth Raizman - Raizman, David
An exploration of the parallel development of product and graphic design from the 18th century to the 21st, considering the relationship between design and manufacturing, and the technological, social and commercial context in which this relationship developed. The effects of a vastly enlarged audience for the products of modern design and the complex dynamic of mass consumption are also discussed. Part of this dynamic reveals that products serve as signs for desires that have little or nothing to do with need or function. The book also explores the impact of new man-made industrial materials on modern design - from steel to titanium, plywood to plastic, cotton to nylon, wire to transistors and microprocessors to nanotubes. The research, development and application of these technologies is shown as depending upon far-reaching lines of communication stretching across geographical and linguistic boundaries.